REGIONS OF RUSSIA IN THE CORONAVIRUS PANDEMIC - N. Z. Zotikov (Вестник университета, 2020)
The relevance of the study is due to the fact that the solution of the tasks facing the country is impossible without strengthening the role of the regions. Russia is characterized by deep differentiation of regions in terms of development level, which is due to the influence of natural and climatic conditions, uneven distribution of minerals, labor resources, external factors, etc. To these mentioned factors, another one was added – coronavirus. The purpose and objectives of the study are to determine the role and place of regions in their socio-economic  situation, assessing them using the indicators used by the rating agency RIA Rating, taking into account modern challenges. The practical significance of the study is as follows. The concentration of competitive advantages in some regions and their lack in others, which depend on the population`s incomes, exacerbate social inequality. At  the present stage of development, taking into account the changed economic situation in the world, the issues of  economic security of the regions are of particular importance. The article provides ratings of Federal districts,  regions by the level of their socio-economic situation for 2019 in comparison with 2018, for the 1st quarter, 9 months of 2020 in a pandemic.